(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2023)
The present study was carried out to determine the phytochemical constituents, physicochemical values, antioxidant activity and in-vitro anti-inflammatory activity of Rheum nobile Hook.f & Thomson according to the standard pharmacopoeial method, which is traditionally used by the indigenous communities of the Sikkim Himalayan region for the treatment of rheumatoid arthritis. The phytochemical investigation revealed the presence of various secondary metabolites such as flavonoids, tannins, phenols, steroids, phlobatannins, saponins, anthraquinones and glycosides. The in-vitro anti-inflammatory activity of the plant extract assessed by HRBC membrane stabilisation and protein denaturation methods is found to effectively inhibit HRBC haemolysis and protein denaturation in a dose-dependent manner. The present finding provides evidence for the antioxidant and anti-inflammatory activity of the plant extract, which approves the traditional statements of Rheum nobile as an anti-arthritic agent.